Effect of Socio-Demographic Characteristics on Level of Zinc in Serum of Adults in Najaf - Ali Hassouni, Sabreen; Taresh Ahmed, Jabbar; Jasim Mohammed, Salam (University of Thi-Qar Journal of Science, 2023)
Background: Zinc is an essential trace element in maintaining human health. Zinc deficiency has many adverseeffects on the body's growth and validity and delays the  individuals’ daily performance of duties. The study aimed: tofind the association between serum zinc levels and different  socio-demographic factors.Material and Methods: A crosssectional study was conducted to achieve the study's aim from November 2021 to May 2022. The size of sample comprises 140 participants. All study members were adults ages ranging from (18-65) years taken randomly from Al-NajafGovernorate. The data was collected by estimating serum zinc and using a simple questionnaire, then analyzed using astatistical program.Results: The association between serum zinc with educational level and monthly income was a  significant p-value (0.048 and 0.027, respectively). Other sociodemographic characteristics were not significant.Conclusion:The study concluded that educational level and monthly income could affect serum zinc level more than Other sociodemographic characteristics.